2007
DOI: 10.1093/jxb/erl302
|View full text |Cite
|
Sign up to set email alerts
|

Drought constraints on C4 photosynthesis: stomatal and metabolic limitations in C3 and C4 subspecies of Alloteropsis semialata

Abstract: The C4 photosynthetic pathway uses water more efficiently than the C3 type, yet biogeographical analyses show a decline in C4 species relative to C3 species with decreasing rainfall. To investigate this paradox, the hypothesis that the C4 advantage over C3 photosynthesis is diminished by drought was tested, and the underlying stomatal and metabolic mechanisms of this response determined. The effects of drought and high evaporative demand on leaf gas exchange and photosynthetic electron sinks in C3 and C4 subsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
109
3
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(140 citation statements)
references
References 63 publications
15
109
3
8
Order By: Relevance
“…This suggested that C 4 plants have higher carbon sequestration under drought conditions. These results are consistent with previous research that C 4 plants have an advantages in Pn in drought conditions compared with C 3 plants [30,44,45] because the C 4 CO 2 -concentrating mechanism offers C 4 photosynthesis a greater buffering capacity against CO 2 shortages due to partial stomatal closure under water stress [46]. However, drought increased C 3 WUE overall, but tended to decrease C 4 WUE (Figure 1).…”
Section: Photosynthetic Pathwayssupporting
confidence: 92%
“…This suggested that C 4 plants have higher carbon sequestration under drought conditions. These results are consistent with previous research that C 4 plants have an advantages in Pn in drought conditions compared with C 3 plants [30,44,45] because the C 4 CO 2 -concentrating mechanism offers C 4 photosynthesis a greater buffering capacity against CO 2 shortages due to partial stomatal closure under water stress [46]. However, drought increased C 3 WUE overall, but tended to decrease C 4 WUE (Figure 1).…”
Section: Photosynthetic Pathwayssupporting
confidence: 92%
“…Este mecanismo concentra CO 2 próximo à enzima Rubisco, o que permite sua maior atividade como carboxilase e resulta em maior eficiência do uso de água e de nitrogênio e na ausência de fotorrespiração (Sage & Kubien, 2007). Dessa forma, a L M da fotossíntese pode estar relacionada a alterações na atividade enzimática da PEPcase e da Rubisco, com regeneração dos substratos das enzimas e transporte de elétrons (Ripley et al, 2007;Carmo-Silva et al, 2008;Ghannoum, 2009;Soares-Cordeiro et al, 2010). A eficiência aparente de carboxilação da PEPcase (V pmáx ) foi menor do que a da testemunha, no primeiro dia, em todos os tratamentos.…”
Section: Resultsunclassified
“…Our results could therefore be a reflection of direct effects of leaf water status on A mediated via non-stomatal (metabolic) limitations that are independent of P i (Lawlor & Tezara, 2009). Furthermore, it has been demonstrated that C 4 plants are sensitive to non-stomatal limitations mediated via plant water status, and the effect was greater than in C 3 leaves (Ripley et al, 2007;Taylor et al, 2011). Alternatively the variance introduced into the calculation of P i from both H 2 O and CO 2 flux measurements could have diminished the power of statistical analyses for P i .…”
Section: Discussionmentioning
confidence: 99%